(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
NGO leaders often face extraordinary challenges both at a personal and organisational level. They work for long hours with limited resources in uncertain and volatile political and economic environment to help the most marginalised and disadvantaged members of their communities. NGO leaders are often isolated and lack support of society. There is talk of a leadership deficit, because of the shortage of talented leaders and in non-profit making sector. As a result there is some urgency to develop a new generation of leaders, and to provide relevant support to existing and future leaders. Leadership development programmes designed for NGO leaders must incorporate best practice and current experience rather than rehashing tired, traditional approaches to leadership training. This paper examines the role of leadership development in NGO and assesses some of the challenges in developing a new generation of NGO leaders. The paper draws on the analysis of new and existing research into the dimensions of NGO leadership highlighting the importance of both individual attributes and contextual relevance. Effective NGO leaders are able to balance a range of competing pressures from different stakeholders in ways that do not compromise their individual identity and values. Leadership development programmes therefore need to focus on both the values and identity of individual leaders while also assisting leaders understand and proactively respond to the rapidly changing external environment. Additionally, the research is focussed on the experience of workplace cultures which provide the context for the delivery of human services, and have also discussed the current charitable human services paradigm. The paper also focuses on urgent need to build the capacity of NGOs to develop their leadership capability. The faith and secularity of each NGO also presented opportunities to map organisational intention around leadership, spirituality, ethics and values such that further research opportunities will be highlighted across the results. Unless systems and processes to support this work are put in place then the apocryphal warning that tress die from up will have more than a ring of truth in it. Desk research will be done and will be carefully analysis of data from secondary sources will be made to make this research paper useful for the NGOs.